Ciencia e investigación agraria 2019
DOI: 10.7764/rcia.v46i3.2062
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Unconventional Oils on in Vitro Rumen Methane Production and Fermentation

Abstract: M. Embaby, M. Günal, and A. AbuGhazaleh. 2019. Effect of unconventional oils on in vitro rumen methane production and fermentation. Cien. Inv. Agr. 46(3): 276-285. The effects of unconventional oils high in polyunsaturated fatty acids (PUFAs) (blackberry, blueberry, raspberry, pomegranate, black seed and hemp oils) on in vitro rumen fermentation and methane (CH 4 ) production were examined in a 24-h batch culture experiment. Treatments consisted of a control (no oil supplement), a control plus corn oil, or a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 35 publications
2
7
0
Order By: Relevance
“…Whole hempseed was 8% more effective at reducing methane than linseed but comparable to coconut oil (115). Embaby et al (101) recorded a 10% decrease in methane production for hempseed oil compared to corn oil. Methane production reduction is attributed to high PUFA content in hempseed oil, which suppresses protozoa and acts as hydrogen sink through biohydrogenation (115,116), with α-linolenic acid being a more potent anti-methanogen than linoleic acid (117).…”
Section: Nitrogen and Methane Emissionsmentioning
confidence: 98%
See 3 more Smart Citations
“…Whole hempseed was 8% more effective at reducing methane than linseed but comparable to coconut oil (115). Embaby et al (101) recorded a 10% decrease in methane production for hempseed oil compared to corn oil. Methane production reduction is attributed to high PUFA content in hempseed oil, which suppresses protozoa and acts as hydrogen sink through biohydrogenation (115,116), with α-linolenic acid being a more potent anti-methanogen than linoleic acid (117).…”
Section: Nitrogen and Methane Emissionsmentioning
confidence: 98%
“…Hempseed oil has a high PUFA content (Table 4), which may have an inhibitory effect on ruminal fibrolytic bacteria (113,114). Hempseed oil reduces ruminal acetate production, which is generally an indicator of decreased fiber digestibility (101). Unaffected propionate production is an indicator of little or no influence on carbohydrate degradation (101).…”
Section: Nutrient Digestibilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding to the latter, it was reported (33) that hempseed oil is more efficient in the inhibition of methanogens since it has more terpenes, polyphenols and lignin. Similarly, Embaby et al (40) found a 10 % reduction in methane production when using hempseed oil and compared to corn oil. However, Patra et al (41) affirmed that reductions in methane production are associated to the presence of polyunsaturated fatty acids (PUFA) than the presence of cannabinoids; these fatty acids were not evaluated in this study.…”
Section: Resultsmentioning
confidence: 91%